TECHNOLOGY-BASED POPULATION ADMINISTRATION SERVICE INNOVATION: AN ANALYSIS OF IMPLEMENTATION AND CHALLENGES IN LOCAL GOVERNMENTS - Kayla Alif Ruzaqila; Teguh Yuwono (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Public service innovation through technology adoption has become imperative for local governments in Indonesia. This study examines the implementation of a self-service kiosk technology for population administration services in Jepara Regency, Central Java. Using qualitative methods with interviews and document analysis, this research evaluates implementation effectiveness through five key dimensions: policy content appropriateness, implementer suitability, target precision, environmental compatibility, and process adequacy. Findings reveal that while the innovation successfully addresses long queuing issues and improves service efficiency, significant challenges persist including limited infrastructure readiness in remote areas, digital literacy gaps among citizens, and incomplete standard operating procedures for support staff. The study demonstrates that technology-driven public service innovations require comprehensive planning beyond procurement, including human resource development, infrastructure support, and formal institutional arrangements. This research contributes to understanding e-government implementation at local level and provides practical recommendations for policymakers pursuing digital transformation in public services.